Authoring Systems Delivering Reusable Learning Objects - Schreurs, Jeanne; Dalle, Rik; Sammour, George Nicola (International Journal of Emerging Technologies in Learning (iJET), 2009)
A three layer e-learning course development model has been defined based on a conceptual model of learning content object. It starts by decomposing the learning content into small chunks which are initially placed in a hierarchic structure of units and blocks. The raw content components, being the atomic learning objects (ALO), were linked to the blocks and are structured in the database. We set forward a dynamic generation of LO’s using re-usable e-learning raw materials or ALOâ??s In that view we need a LO authoring/ assembling system fitting the requirements of interoperability and reusability and starting from selecting the raw learning content from the learning materials content database. In practice authoring systems are used to develop e-learning courses. The company EDUWEST has developed an authoring system that is database based and will be SCORM compliant in the near future.